A Theranostic Small-Molecule Prodrug Conjugate for Neuroendocrine Prostate Cancer - Paulina Gonzalez; Sashi Debnath; Yu-An Chen; Elizabeth Hernandez; Preeti Jha; Marianna Dakanali; Jer-Tsong Hsieh; Xiankai Sun (MDPI AG, 2023)
After androgen deprivation therapy, a significant number of prostate cancer cases progress with a therapy-resistant neuroendocrine phenotype (NEPC). This represents a challenge for diagnosis and treatment. Based on our previously reported design of theranostic small-molecule prodrug conjugates (T-SMPDCs), herein we report a T-SMPDC tailored for targeted positron emission tomography (PET) imaging and chemotherapy of NEPC. The T-SMPDC is built upon a triazine core (TZ) to present three functionalities: (1) a chelating moiety (DOTA: 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) for PET imaging when labeled with 68Ga (t1/2 = 68 min) or other relevant radiometals; (2) an octreotide (Octr) that targets the somatostatin receptor 2 (SSTR2), which is overexpressed in the innervated tumor microenvironment (TME); and (3) fingolimod, FTY720-an antagonist of sphingosine kinase 1 that is an intracellular enzyme upregulated in NEPC. Polyethylene glycol (PEG) chains were incorporated via conventional conjugation methods or a click chemistry reaction forming a 1,4-disubstituted 1,2,3-triazole (Trz) linkage for the optimization of in vivo kinetics as necessary. The T-SMPDC, DOTA-PEG3-TZ(PEG4-Octr)-PEG2-Trz-PEG3-Val-Cit-pABOC-FTY720 (PEGn: PEG with n repeating ethyleneoxy units (n = 2, 3, or 4); Val: valine; Cit: citrulline; pABOC: p-amino-benzyloxycarbonyl), showed selective SSTR2 binding and mediated internalization of the molecule in SSTR2 high cells. Release of FTY720 was observed when the T-SMPDC was exposed to cathepsin B, and the released FTY720 exerted cytotoxicity in cells. In vivo PET imaging showed significantly higher accumulation (2.1 ± 0.3 %ID/g; p = 0.02) of [68Ga]Ga-DOTA-PEG3-TZ(PEG4-Octr)-PEG2-Trz-PEG3-Val-Cit-pABOC-FTY720 in SSTR2high prostate cancer xenografts than in the SSTR2low xenografts (1.5 ± 0.4 %ID/g) at 13 min post-injection (p.i.) with a rapid excretion through the kidneys. Taken together, these proof-of-concept results validate the design concept of the T-SMPDC, which may hold a great potential for targeted diagnosis and therapy of NEPC.